Pelatihan Akuntansi bagi Entitas tanpa Akuntabilitas Publik Berbasis Usaha Mikro pada PKK RW 06 Kelurahan Serdang Jakarta Pusat - Mulyaning Wulan Wulan; Ummu Salma Al Azizah (SYUKUR (Jurnal Inovasi Sosial dan Pengabdian Masyarakat), 2018)
The role of government in the development of Micro Small and Medium Enterprises (MSMEs) has been proven by the issuance of Financial Accounting Standards for Non Public Accountantless Entities as well as Accounting Standards for Micro, Small and Medium Enterprises (MSMEs Standard) issued by the Indonesian Institute of Accountants (IAI). The application of standards that have been made by the government requires the right mediator. The most higher education institutions (universities) have human resources (HR) that can help the government to transfer the information. This can be done through Community Service which is one of the Tri Darma Program in University. In general problems in business management for micro enterprises are very diverse. The problems that occur include: marketing (marketing), financing, location, security and making simple financial statements for their entity. Training of financial statement preparation is an offer to answer the problem. The number of micro enterprises in RW 06 area is potential to be assisted by the financial management. Good management requires the support of the business report, in this case is the financial statements. Society needs knowledge to make reporting in accordance with existing standards.